EVALUATION OF ANTIBIOTIC USE IN PEDIATRIC BRONCHOPNEUMONIA INPATIENTS AT BHAYANGKARA SARTIKA ASIH BANDUNG HOSPITAL - Sartika, Venti
Antibiotics are drugs used in infections caused by bacteria. Antibiotics that are not used wisely can trigger resistance problems. The existence of antibiotic resistance causes a decrease in the ability of the antibiotic to treat infections. Pneumonia is the single largest infectious cause of death in children worldwide. Based on the above problems, this study was conducted to evaluate the use of antibiotics quantitatively and qualitatively. The type of research was descriptive analytic with a cross-sectional approach and data collection was done retrospectively using patient medical record data. Data collection was carried out using the total sampling method with the results of 153 patients who met the inclusion criteria. Antibiotic evaluation was carried out quantitatively using the Anatomy Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method and the 90% DU segment, while qualitative evaluation used the Gyssens Flowchart method. Quantitative evaluation results showed ampicillin-sulbactam had the highest DDD/100 patient-days at 9.4 DDD/100 patient-days, followed by ceftriaxone at 8.82 DDD/100 patient-days and cefotaxime at 4.33 DDD/100 patient-days. For the 90% DU segment results, there were 3 antibiotics included in the 90% DU segment, namely ampicillin-sulbactam, ceftriaxone, and cefotaxime. The results of the Gyssens evaluation showed that 95.65% of antibiotics were used wisely, 3.91% of antibiotics fell into category IIA, namely the use of antibiotics inappropriate doses (subdose), and 0.43% fell into category IVA, namely there are other alternatives that are more ef ective. The evaluation results were analyzed using chi-square and showed no significant relationship between rational antibiotic administration and therapeutic outcomes. Risk factor analysis showed that there was no association between gender, age, nutritional status, length of stay, and number of diagnoses with clinical outcomes.